2022
DOI: 10.1186/s12873-022-00606-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive performances of ALS and BLS termination of resuscitation rules in out-of-hospital cardiac arrest for different resuscitation protocols

Abstract: Background Resuscitation guidance has advanced; however, the predictive performance of the termination of resuscitation (TOR) rule has not been validated for different resuscitation protocols published by the American Heart Association (AHA). Methods A retrospective study validating the basic life support (BLS) and advanced life support (ALS) TOR rules was conducted using an Utstein-style database in Tainan city, Taiwan. Adult patients with nontrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…First-pass title and abstract screening yielded 131 potentially eligible studies. After the second-pass full-text screening, 43 studies remained (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First-pass title and abstract screening yielded 131 potentially eligible studies. After the second-pass full-text screening, 43 studies remained (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We identified very low-certainty evidence (downgraded for risk of bias, inconsistency, imprecision, indirectness, and publication bias) from 33 observational studies involving 927 534 cases. These studies reported external data validations of 17 TOR rules.…”
Section: Resultsmentioning
confidence: 99%
“…The hyperthermic group had a longer door-to-catheterization time. There was no community outbreak of COVID-19 during the study period [ 17 , 18 ] and none of the patients that were included in this study had COVID infection. We suspected that the presence of hyperthermia may have the clinicians to take precautions and perform more laboratory examination or imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…Data were retrospectively retrieved from electronic medical records and were deidentified for analysis. There was no community outbreak of COVID-19 in Tainan city during the study period [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Basic life support (BLS) refers to a package of care that first responders, healthcare providers, and public safety professionals provide to anyone experiencing a lifethreatening condition to increase the victim's chance of survival. [1,2] Lifesaving action can be delivered anywhere depending on where a life-threatening event such as road traffic injuries, choking and respiratory failure accidents can occur.…”
Section: Introductionmentioning
confidence: 99%